Alterations in morphology and hepatorenal indices in rats subacutely exposed to bitumen extract. (20th October 2016) - Otuechere, Chiagoziem A.; Adesanya, Oluseyi; Otsupius, Precious; Seyitan, Nathaniel
Abstract: Bitumen is a complex mixture of dense and extremely viscous organic liquids produced by distillation of crude oil during petroleum refining. Nigeria has a large deposit of natural bitumen, yet to be fully exploited. Discharges of petroleum hydrocarbons and other petroleum-derived products have caused environmental pollution and adverse human health effects in several oil-rich communities. In this study, bitumen obtained from a seepage source in Agbabu, the town of first discovery, was used in sub-acute toxicity studies in a rat experimental model, in order to assess potential health risks posed to local populace sequel to full exploitation of bitumen. Dosages were chosen to accommodate low to high cases of environmental exposures. Male Wistar rats were administered, per os, dosages of bitumen extract at 5, 3, 2, and 1 mg/kg body weight. Following euthanasia 28 days later, histological findings revealed severe portal congestion and cellular infiltration in the liver, while in the kidney there were protein casts in the tubular lumen. The relative liver and kidney weights in the 5 mg/kg groups were 34% and 40% higher than in the controls, with a concomitant decrease in food and water consumption. Furthermore, plasma clinical analyses revealed marked elevation in aspartate aminotransferase and triglycerides levels in bitumen extract-intoxicated rats. The results indicate the potential hepatorenal toxicity in adult rats following repeated exposure to bitumen extract.